Implementation of Multicultural Education in Building Harmonization and Tolerance in the Midst of the Diversity of Indonesian Society - Siregar, Abd. Amri (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: Multicultural education plays a crucial role in building harmony and tolerance, ensuring a peaceful and respectful life in a multicultural society. This study aims to describe and analyze the implementation of multicultural education in building harmony and tolerance amidst the diversity of Indonesian society. Using a descriptive qualitative approach and content analysis to collect data from various sources, the research findings indicate that harmonization involves recognizing and respecting cultural, religious, and value diversity within society. Meanwhile, tolerance involves an open attitude and appreciation for differences, without compromising individual human rights. The importance of multicultural education and a better understanding of each individual's culture and religion are recognized as key factors in creating harmony and tolerance. Thus, it can be concluded that the implementation of multicultural education can build harmony and tolerance amidst the diversity of Indonesian society. Therefore, it is recommended that to build harmony and tolerance amidst the diversity of Indonesian society, the implementation of multicultural education in Indonesian schools should be increased.Keywords: Implementation of Multicultural Education, Harmonization, Tolerance, and Community Diversity. Abstrak: Pendidikan multikultural memiliki peran penting dalam membangun harmonisasi dan toleransi dalam memastikan kehidupan yang damai dan saling menghormati di dalam masyarakat multikultural. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis tentang implementasi pendidikan multikultural dalam membangun harmonisasi dan toleransi di tengah keberagaman masyarakat Indonesia. Menggunakan pendekatan kualitatif deskriptif dan analisis konten untuk mengumpulkan data dari berbagai sumber. Temuan penelitian menunjukkan bahwa harmonisasi melibatkan pengakuan dan penghargaan terhadap keragaman budaya, agama, dan nilai-nilai di dalam masyarakat. Sementara itu, toleransi melibatkan sikap terbuka dan penghargaan terhadap perbedaan, tanpa mengorbankan hak asasi individu. Pentingnya pendidikan multikultural dan pemahaman yang lebih baik tentang budaya dan agama masing-masing individu diakui sebagai faktor kunci dalam menciptakan harmoni dan toleransi. Dengan demikian dapat disimpulkan bahwa implementasi pendidikan multikultural dapat membangun harmonisasi dan toleransi di tengah keberagaman masyarakat Indonesia. Sehingga dapat disarankan untuk dapat membangun harmonisasi dan toleransi di tengah keberagaman masyarakat Indonesia, maka tingkatkan implementasi pendidikan multikultural di sekolah Indonesia.Kata Kunci: Implementasi Pendidikan Multikultural, Harmonisasi, Toleransi, Keberagaman Masyarakat.